Sensitivity Enhancement of Silicon-on-Insulator Multipath Ring Resonator using Gold Nanodisk for Sensor Application - Dicky, Gabriel; Taufiqurrahman, Shidqie; Estu, Topik Teguh; Wijayanto, Yusuf Nur; Manurung, Robeth Viktoria; Mahmudin, Dadin; Anshori, Isa; Daud, Pamungkas (UI Scholars Hub, 2020)
Currently, environmental degradation caused by heavy metals has become a serious concern of many countries. To monitor the concentration of heavy metals in the environment, an in-situ sensor that can measure in real time and has high quality, sensitivity, and flexibility is essential. We proposed a modified multipath ring resonator (MPRR) based on silicon-on-insulator technology with additional gold nanodisk (GND) on top of the ring to increase its sensitivity. To prove the effect of GND on the sensitivity of the modified MPRR, finite-difference time-domain simulations were conducted. Results showed that the average sensitivity of the modified MPRR was 675 nm/RIU, where RIU corresponds to the refractive index unit, higher than that of the unmodified MPRR (171 nm/RIU). Moreover, compared with the single ring structure, the proposed design had better sensitivity. We believe that our proposed approach for the modification of MPRR is suitable for application to optical sensor development.